Tumor-associated macrophages: orchestrators of cholangiocarcinoma progression - Chen, Fei; Sheng, Jian; Li, Xiaoping; Gao, Zhaofeng; Hu, Lingyu; Chen, Minjie; Fei, Jianguo; Song, Zhengwei (Frontiers in Immunology, 2024)
Cholangiocarcinoma (CCA) is a rare but highly invasive cancer, with its incidence rising in recent years. Currently, surgery remains the most definitive therapeutic option for CCA. However, similar to other malignancies, most CCA patients are not eligible for surgical intervention at the time of diagnosis. The chemotherapeutic regimen of gemcitabine combined with cisplatin is the standard treatment for advanced CCA, but its effectiveness is often hampered by therapeutic resistance. Recent research highlights the remarkable plasticity of tumor-associated macrophages (TAMs) within the tumor microenvironment (TME). TAMs play a crucial dual role in either promoting or suppressing tumor development, depending on the factors that polarize them toward pro-tumorigenic or anti-tumorigenic phenotypes, as well as their interactions with cancer cells and other stromal components. In this review, we critically examine recent studies on TAMs in CCA, detailing the expression patterns and prognostic significance of different TAM subtypes in CCA, the mechanisms by which TAMs influence CCA progression and immune evasion, and the potential for reprogramming TAMs to enhance anticancer therapies. This review aims to provide a framework for deeper future research.